Research as Informal and Mutual Learning: Reflections on Two Feminist Studies in Nigeria. - Olutoyin Mejiuni (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2013)
Although all research involves knowledge production processes; research activities that explore the real life experiences of adult participants are also learning or educational interactions in and of themselves. This article focuses on the author's reflections on two feminist studies that she carried out in Nigeria that support this position. These educational interactions are reflected in her discussion of the framework on which her studies are based, the context of these studies, the identity politics of participants, and the enhancement and limitations (informal and mutual) learning among many participants and the researcher as a participant-observer.